Answer:
45
Step-by-step explanation:
Answer:
X=-1
Step-by-step explanation:
0=2x+2
subtract 2 out
-2 = 2x
divide 2 on both sides x = -1
Answer:
The solution to this question is 39
Step-by-step explanation:
Given that :
√(3x+7)+2√(x-8)=0.
√(3x+7)=-2√(x-8) (i)
square of the equation (i)
Then
(√(3x+7))^2=(-2√(x-8))^2
we know that √a*√a=(√a)^2=a So,
(3x+7)=4(x-8)
3x+7=4x-32 //multiply by 4
32+7=4x-3x exchange the value.
39=1x
x=39.
I will try my best to assist you with your question ,
First we must divide the amount by 2
334/2 = 167
Now we add 16
167 + 16=183
So, the girl spent $183
Wow, she is spoiled!
Hope I helped!
Good Luck!
Answer:
![20x^{4}-39x^{3} +26x^{2}-6x\\](https://tex.z-dn.net/?f=20x%5E%7B4%7D-39x%5E%7B3%7D%20%2B26x%5E%7B2%7D-6x%5C%5C)
Step-by-step explanation:
Multiply the two polynomials by multiplying each term
![(5x^{2} -6x+2)(4x^{2} -3x)\\5x^2*4x^2+5x^2(-3x)+(-6)*4x^2+(-6x)(-3x)+2*4x^2+2(-3x)\\20x^{4}-39x^{3} +26x^{2} -6x\\](https://tex.z-dn.net/?f=%285x%5E%7B2%7D%20-6x%2B2%29%284x%5E%7B2%7D%20-3x%29%5C%5C5x%5E2%2A4x%5E2%2B5x%5E2%28-3x%29%2B%28-6%29%2A4x%5E2%2B%28-6x%29%28-3x%29%2B2%2A4x%5E2%2B2%28-3x%29%5C%5C20x%5E%7B4%7D-39x%5E%7B3%7D%20%20%2B26x%5E%7B2%7D%20-6x%5C%5C)